Taxonomic Revision of Solorina (Peltigeraceae, Ascomycota), Reveals a New Genus and Three New Species - Ting Zheng; Lisong Wang; Min Ai; Yuxin Gan; Rong Fan; Yingjun Zhang; Fiona Ruth Worthy; Jizhen Jin; Wenping Meng; Shengbang Zhang; Xinyu Wang (Journal of Fungi)
The lichen genus Solorina exhibits significant morphological and chemical variations between species. Recent molecular studies have demonstrated that Solorina is polyphyletic, underscoring the need for a comprehensive taxonomic revision. Phylogenetic analyses employing Bayesian methods and Maximum Likelihood approaches based on three molecular loci (nrITS, nrLSU, mtSSU) revealed that species of Solorina segregate into two distinct clades. The first clade includes species characterized by bright orange lower surfaces that contain secondary metabolites, notably solorinic acid. The type species, Solorina crocea, is retained in the genus Solorina. The second clade encompasses species with white or brownish lower surfaces; most species lack secondary metabolites and are now classified as a new genus, Pseudosolorina. As a result of this taxonomic revision, two species: S. crocea and S. crocoides remain in the genus Solorina. Five species with white or brownish lower surfaces were transferred to the new genus Pseudosolorina, which consists of three newly described species and five new combinations. Four species previously described as Solorina: S. embolina, S. fuegiensis, S. octospora, and S. platycarpa have morphology consistent with Pseudosolorina, but are currently retained in Solorina due to the absence of supporting DNA sequence data. A key to Solorina and Pseudosolorina is provided. The spores of S. crocea exhibit wall ornamentation featuring rounded papillae, which are distinct from those of Pseudosolorina. Molecular data and morphological characters also indicate that both Solorina and Pseudosolorina engage in symbiotic associations with photobionts cyanobacteria Nostoc and chlorophytes Coccomyxa or Asterochloris.